Computer-assisted evaluation system for volleyball referee's executive judgment - Kao, S.; Wu, C.; Chen, C. (International Journal of Computer Science in Sport, 2009)
The purpose of this study is to develop an evaluation system for the executive judgment of volleyball referees. We present computer-assisted techniques to digitalize volleyball games, make judgments, and generate evaluation results. Through the help of senior volleyball referees, we first make classification to the recorded video volleyball games according to various foul situations and apply VideoStudio for test data editing. Through the interface of the computer-assisted evaluation system, times and correctness of judgments are recorded, and corresponding scores are prompted immediately after a test is over. The feasibilityof this system is validated, as ten qualified volleyball referees of level A, B, and C are chosen for test participators. Statistical analyses of confidence and correlation are also included. According to the Pearson's coefficient analysis, the results from three co-related test sets show that the computer-assisted evaluation system for volleyball referee`s executive judgment is highly reliable in both test-retest form and alternate form. In addition to serve for the volleyball referees evaluation, the system can also be used as a training purpose to improve the performance of judgment technique.